2007
DOI: 10.2140/jomms.2007.2.1121
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel numerical model quantifying cell deformation in encapsulated alginate structures

Abstract: Mechanical forces not only deform cells, but also alter their functions due to biological responses. While current biomanufacturing processes are capable of producing tissue scaffolds with cells encapsulated, it is essential to understand cell responses to process-induced mechanical disturbances. In this study the stresses and deformations of encapsulated cells under compressive loads are quantified via a multilevel nonlinear finite element approach. The macrolevel model is used to mechanically characterize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Flowever, screw-driven extrusion can generate larger pressure drops along the nozzle, which can potentially be harmful for loaded cells. Their rheology study and cell viability assay were per formed to investigate cell damage due to mechanical stress during the printing process [83], They found that cell viability was influ enced by material concentration, dispensing pressure, material flow rate and nozzle geometry. The main advant age of using a pneumatically driven system is the various types and viscosities of bioinks that can be dispensed by adjusting the pressure and valve gating time.…”
Section: Extrusion-basedmentioning
confidence: 99%
“…Flowever, screw-driven extrusion can generate larger pressure drops along the nozzle, which can potentially be harmful for loaded cells. Their rheology study and cell viability assay were per formed to investigate cell damage due to mechanical stress during the printing process [83], They found that cell viability was influ enced by material concentration, dispensing pressure, material flow rate and nozzle geometry. The main advant age of using a pneumatically driven system is the various types and viscosities of bioinks that can be dispensed by adjusting the pressure and valve gating time.…”
Section: Extrusion-basedmentioning
confidence: 99%
“…12 compares the distributions of the maximum strain from uniform material property and random material property analyses; the differences are 2 and 25% for the mean value and standard deviation, respectively. Furthermore, in our previous study (Nair et al, 2007), the cell diameter was randomly varied from 20 to 40 mm, and the resulting changes in stresses and strains were observed as 1% of the mean value and 5% of the standard deviation. Finally, micrographic images of tissue constructs suggest that the encapsulated endothelial cells tend to be spherical (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…It is noted that the SED of cell is close to the mean value obtained from the multi-cellular analyses. The results from the 3D analyses were also compared with those from our previous 2D analyses (Nair et al, 2007). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cell-embedded 3D printing with microextrusion includes a d ispensing system that uses pneumatic or mechanical forces to extrude bioink in a line ( ) [29][30][31][32][33] . It is one of the most common cell printing methods owing to its accessibility and versatility in printing 3D structures.…”
Section: Microextrusion-based Cell Printingmentioning
confidence: 99%